Elliptical Fourier analysis of molar outlines in Late Pliocene Parapapio whitei from Makapansgat Limeworks, South Africa - Alexander C. Kim; Frank L’Engle Williams (Anthropological Review)
Introduction: Alongside Australopithecus africanus at Makapansgat South Africa, dated to nearly 3 million years before present, are remnants of Parapapio (Cercopithecinae). The extreme variability of this fossil assemblage has stymied efforts to specify the taxon parameters for Parapapio, which are attributed to at least three species.